2023
DOI: 10.7759/cureus.35030
|View full text |Cite
|
Sign up to set email alerts
|

Management of Heart Failure With Preserved Ejection Fraction in Elderly Patients: Effectiveness and Safety

Abstract: The proportion of the elderly population continues to increase due to the global increase in longevity. Heart failure with preserved ejection fraction (HFpEF) is common in the elderly due to cellular aging, myocardial stiffness, and multiple comorbidities. This age group is often under-represented in clinical trials. In this narrative review, we looked into the latest evidence-based lines of management of HFpEF in this vulnerable cohort. In this narrative review, we brought the latest evidence on the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Comprehensive clinical outcomes: Comprehensive clinical outcomes were analyzed in all 16 trials[ 15 - 17 ], and the heterogeneity test showed no significant heterogeneity among trials ( P = 0.17, I 2 = 25%). Therefore, the fixed-effects model was chosen for analysis[ 18 ]. The results unveiled a marked difference between the two groups (RR = 3.20; 95%CI = 2.40, 4.26; P < 0.00001), indicating that TCM combined with CWM treatment could improve the comprehensive clinical outcomes of patients (Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Comprehensive clinical outcomes: Comprehensive clinical outcomes were analyzed in all 16 trials[ 15 - 17 ], and the heterogeneity test showed no significant heterogeneity among trials ( P = 0.17, I 2 = 25%). Therefore, the fixed-effects model was chosen for analysis[ 18 ]. The results unveiled a marked difference between the two groups (RR = 3.20; 95%CI = 2.40, 4.26; P < 0.00001), indicating that TCM combined with CWM treatment could improve the comprehensive clinical outcomes of patients (Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Age-related mechanisms play an important role in the pathophysiology of HFpEF ( 49 ). Older patients are at higher risk of side effects from HF medications ( 50 ). The proportion of men and women in the studies we included was fairly evenly distributed.…”
Section: Discussionmentioning
confidence: 99%
“…The aging process and the above comorbidities may induce chronic systemic inflammation, leading to myocardial remodeling and HFpEF [16]. Owing to the specific characteristics of the elderly age group and the presence of various comorbidities with overlapping symptoms, HF is often underdiagnosed in these patients [17].…”
Section: Old Age and Hfpefmentioning
confidence: 99%